Integrated sustainable childhood Pneumonia and infectious disease reduction in Nigeria (INSPIRING) through whole system strengthening in Jigawa, Nigeria: study protocol for a cluster randomised controlled trial (2022)
Background: Child mortality remains unacceptably high, with Northern Nigeria reporting some of the highest rates globally (e.g. 192/1000 live births in Jigawa State). Coverage of key protect and prevent interventions, such as vaccination and clean cooking fuel use, is low. Additionally, knowledge, care-seeking and health system factors are poor. Therefore, a whole systems approach is needed for sustainable reductions in child mortality. Methods: This is a cluster randomised controlled trial, with integrated process and economic evaluations, conducted from January 2021 to September 2022. The trial will be conducted in Kiyawa Local Government Area, Jigawa State, Nigeria, with an estimated population of 230,000. Clusters are defined as primary government health facility catchment areas (n = 33). The 33 clusters will be randomly allocated (1:1) in a public ceremony, and 32 clusters included in the impact evaluation. The trial will evaluate a locally adapted ‘whole systems strengthening’ package of three evidence-based methods: community men’s and women’s groups, Partnership Defined Quality Scorecard and healthcare worker training, mentorship and provision of basic essential equipment and commodities. The primary outcome is mortality of children aged 7 days to 59 months. Mortality will be recorded prospectively using a cohort design, and secondary outcomes measured through baseline and endline cross-sectional surveys. Assuming the following, we will have a minimum detectable effect size of 30%: (a) baseline mortality of 100 per 1000 livebirths, (b) 4480 compounds with 3 eligible children per compound, (c) 80% power, (d) 5% significance, (e) intra-cluster correlation of 0.007 and (f) coefficient of variance of cluster size of 0.74. Analysis will be by intention-totreat, comparing intervention and control clusters, adjusting for compound and trial clustering. Discussion: This study will provide robust evidence of the effectiveness and cost-effectiveness of community-based participatory learning and action, with integrated health system strengthening and accountability mechanisms, to reduce child mortality. The ethnographic process evaluation will allow for a rich understanding of how the intervention works in this context. However, we encountered a key challenge in calculating the sample size, given the lack of timely and reliable mortality data and the uncertain impacts of the COVID-19 pandemic.